Dominant Ideology Reflected In Thoreau's Civil Disobedience: A Critical Discourse Analysis - Weabesa, Ismail, Drs. M. Thoyibi, M. S., Titis Setyabudi, S.S. M.Hum (2015)
The research paper studies about the dominant ideology. The study aims at classifying the structural element, social cognition and dominant ideology of Thoreau in his essay Civil Disobedience. The research paper is descriptive qualitative research. The object of the study is the dominant ideology of Thoreau in his essay Civil Disobedience. The data are the variation of the Thoreau' essay, the data are derived from the Thoreau's Civil Disobedience essay. The researcher applies the Critical Discourse Analysis or CDA in analyzing the data of the study. The result of the research shows that the dominant ideology of Thoreau in his Civil Disobedience essay is democracy ideology. The democracy ideology is as the dominant ideology in Thoreau's Civil Disobedience essay, it is got the effect from the heat circumstance of government in treating his civil. The Thoreau's expression keyword for instance; Justice, Justly, Refuse, Resist, Against, Voting, Rights and Indifference have the closed meaning of the theory which were identified key concepts of democracy by Bühlmann and friends; equality; freedom; and "control".